An unforgettable event: a qualitative study of the 1997–98 El Niño in northern Peru. Issue 2 (April 2014) - Bayer, Angela M.; Danysh, Heather E.; Garvich, Mijail; Gonzálvez, Guillermo; Checkley, William; Álvarez, María; Gilman, Robert H.
<x xml:space="preserve">Abstract</x> During the 1997–98 El Niño, Tumbes, Peru received 16 times the annual average rainfall. This study explores how Tumbes residents perceived the impact of the El Niño event on basic necessities, transport, health care, jobs and migration. Forty‐five individuals from five rural communities, some of which were isolated from the rest of Tumbes during the event, participated in five focus groups; six of these individuals constructed nutrition diaries. When asked about events in the past 20 years, participants identified the 1997–98 El Niño as a major negative event. The El Niño disaster situation induced a decrease in access to transport and health care and the rise in infectious diseases was swiftly contained. Residents needed more time to rebuild housing; recover agriculture, livestock and income stability; and return to eating sufficient animal protein. Although large‐scale assistance minimized effects of the disaster, residents needed more support. Residents' perspectives on their risk of flooding should be considered in generating effective assistance policies and programmes.